Medical Journal of Indonesia Vol.23. Issue 2, May 2014 pp 63-124 - Redaksi (FK Universitas Indonesia, 2014)
- Adhesion Prevention After Tendon Repair - Autoclave Devitalization Effect On Autograft & BMP - Photocoagulation and Bevacizumab in Diabetic REtinopathy - Mortality Score After Pancreaticoduodenectomy - Lesion-only application of permethrin for scabies treatment - Social determinants of perception on tuberculosis - Obesity in intellectualy disabled students in Jakarta - Health and hydration status of workers - Renal artery stenosis in the young - Cost of hemodialysis under health reform system